Analisis perbandingan kinerja keuangan sebelum dan saat terjadi pandemi covid – 19 pada PT. Bumi Serpong Damai tbk. periode 2019 – 2020 - Amalia, Shendy; Mariana, Hana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid - 19 pandemic caused a fairly deep contraction for the Indonesian economy, which also had an impact on the property and real estate sector, where there was a decrease in public interest in housing sales, where PT. Bumi Serpong Damai Tbk. has a main sales segment, namely integrated city. This study aims to find out whether there has been a significant change in financial performance in the period before and during the Covid-19 pandemic at PT. Bumi Serpong Damai Tbk. period 2019 – 2020. The data used in this study includes quarterly financial data for the period 2019 – 2020, while the method used is quantitative descriptive analysis. Data analysis techniques using Descriptive Statistical Test and Wilcoxon Test. The results of this study indicate that there was no significant difference in the financial performance before and during the Covid-19 pandemic at PT. Bumi Serpong Damai Tbk Period 2019 – 2020.